Health Status of Adolescents Residing in Sarjapur PHC Area near Bangalore: A Community-Based Study - Cency Baburajan; Avita Rose Johnson; T Sulekha (Medsci Publications, 2020)
Background: Adolescent health and behaviour patterns in rural areas are changing with increasing exposure to media and internet. This study was conducted to assess health status of adolescents in rural areas covered by Sarjapur Primary Health Centre. Methods: Community-based, cross-sectional study in 25 villages in Bangalore Urban District. Two-staged cluster sampling done. Interview schedule for socio-demographic details and information on illness and health-related behaviours, height and weight measured and haemoglobin estimated using Hemocue. 'Health status' measured by anaemia, nutrition status, reported illness, substance abuse, personal hygiene, diet and physical activity. Chi-square test for association between outcome variables and socio-demographic factors. Results: Of 210 adolescents, 48.1% were anaemic, 63.8% underweight and 21.9% overweight. Anaemia or nutritional status were not associated with socio-demographic variables. Common illnesses were viral fever, respiratory infections and dengue. 16.2% of subjects used tobacco and 1.9% consumed alcohol. Bathing and brushing teeth were inadequate. Skipping meals, junk food, poor intake of fruits and vegetables were common, but physical activity was adequate. Conclusion: Overall health status of rural adolescents was found to be poor. Community level workers must create awareness regarding adolescent health services, treat anaemia, counsel adolescents against tobacco use, and promote healthy diet.